Effect Of White Noise, Binaural Beats And Instrumental Music In Pain Perception During Dental Treatment In Children Aged 6-12 Years - Subhaganesh, M. Nawin; M.D.S., M. Sunil Kumar; M.D.S, Vignesh Guptha; M.D.S, Agisha Raaje; Prassath M.D.S., Narendra; M.D.S, Sudhakar (Journal of Neonatal Surgery, 2025)
Background: Pedodontists approach a child in a dental chair via multiple strategies, and they often use a combination of strategies to address the child’s age, personality and level of dental anxiety. Creating a welcoming and calming musical environment can significantly ease anxiety and improve the overall experience for children during dental treatment. The aim of the study is to measure and compare the influence of white noise, binaural beats and instrumental music on anxiety levels in children undergoing dental treatments. Materials & Methods: The children aged between 6-12 years were chosen and were divided evenly into four groups, each consisting of 20 samples, using a basic random sampling procedure. These are the groupings: Group 1: White noise Group 2: Binaural beats, Group 3: Instrumental music, Group 4: No Audio (control group). Patient anxiety level was evaluated by measuring Wong Baker’s pain scale and pulse rate at intervals before, during & after 10 minutes of dental treatment. Results: White noise exposure to children during dental treatment exhibited better results compared to other groups. The Wong baker scale was restricted to <6 whereas in binaural beats with <8 and instrumental music & control group with a maximum score of 10. There was a significant reduction in the average pulse rate before and after 10 minutes of treatment who were exposed to white noise which was 85.85 ± 2.498 and 82.05 ± 3.220. There were no other groups which exhibited promising results as much as white noise. Conclusion: We found that the effect of white noise was effective in reducing the anxiety of a child in a dental chair during treatment when compared to binaural beats and instrumental music. This proves that the effect of white noise is better and hence can be utilized as one reliable non-pharmacological method to calm a child during dental treatment.